Development of sexual dimorphism in two sympatric skinks with different growth rates. Issue 13 (14th June 2019) - Yang, Chen; Zhao, Jinming; Diaz, Raul E.; Lyu, Nan
Abstract: Sexual size dimorphism (SSD) is widespread in animals, especially in lizards (Reptilia: Squamata), and is driven by fecundity selection, male–male competition, or other adaptive hypotheses. However, these selective pressures may vary through different life history periods; thus, it is essential to assess the relationship between growth and SSD. In this study, we tracked SSD dynamics between a "fading‐tail color skink" (blue tail skink whose tail is only blue during its juvenile stage: Plestiodon elegans ) and a "nonfade color" tail skink (retains a blue tail throughout life: Plestiodon quadrilineatus ) under a controlled experimental environment. We fitted growth curves of morphological traits (body mass, SVL, and TL) using three growth models (Logistic, Gompertz, and von Bertalanffy). We found that both skinks have male‐biased SSD as adults. Body mass has a higher goodness of fit (as represented by very high R 2 values) using the von Bertalanffy model than the other two models. In contrast, SVL and TL for both skinks had higher goodness of fit when using the Gompertz model. Two lizards displayed divergent life history tactics: P. elegans grows faster, matures earlier (at 65 weeks), and presents an allometric growth rate, whereas P. quadrilineatus grows slower, matures later (at 106 weeks), and presents an isometric growth rate. Our findings imply that species‐ and sex‐specific trade‐offs in the allocation of energy to growth and reproduction may cause the growth patterns to diverge, ultimately resulting in the dissimilar patterns of SSD. Abstract : Generally, the blue tail coloration fades with age and is lost at sexual maturation in Genus Plestiodon . The Chinese four‐lined skink retains the blue tail into adulthood postsexual maturity as an exception. To understand the role of tail coloration in generating sexual size dimorphism (SSD) and which factors driving the evolution of blue tail change, we selected two congeneric and sympatric skinks to fit growth curves of morphological traits. We found that both skinks were male‐biased SSD as adult, but they displayed two divergent life history tactics, which implied that species‐ and sex‐specific trade‐offs in the allocation of energy to growth and reproduction cause the growth patterns to diverge, ultimately resulting in the dissimilar patterns.